2017
DOI: 10.1103/physreve.95.010202
|View full text |Cite
|
Sign up to set email alerts
|

Nonvariational mechanism of front propagation: Theory and experiments

Abstract: Multistable systems exhibit a rich front dynamics between equilibria. In one-dimensional scalar gradient systems, the spread of the fronts is proportional to the energy difference between equilibria. Fronts spreading proportionally to the energetic difference between equilibria is a characteristic of one-dimensional scalar gradient systems. Based on a simple nonvariational bistable model, we show analytically and numerically that the direction and speed of front propagation is led by nonvariational dynamics. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Such a term also appears in the Kardar-Parisi-Zhang (KPZ) equation [64] and is also used in a nonvariational version of the SH equation [61]. One also finds µ [5] and SH [72,17] equations. Similar and higher order terms are used in Ref.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such a term also appears in the Kardar-Parisi-Zhang (KPZ) equation [64] and is also used in a nonvariational version of the SH equation [61]. One also finds µ [5] and SH [72,17] equations. Similar and higher order terms are used in Ref.…”
Section: Introductionmentioning
confidence: 96%
“…Employing the energy functional (5) in a conserved gradient dynamics [Eq. ( 4) with Q nc = 0] with f being a quartic polynomial gives the Cahn-Hilliard (CH) equation that describes e.g.…”
Section: Introductionmentioning
confidence: 99%
“…18, i.e., we incorporate a nonequilibrium chemical potential 15 as also frequently done for massconserving Cahn-Hilliard-type dynamics [19][20][21][22] . Such an amended AC equation may be employed to model, e.g., front propagation in a liquid crystal light valve 18 . Second, we couple the AC equation for the order parameter to an evolution equation of a polarisation field P in a similar spirit as in an active phase-field-crystal (PFC) model [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Appendix A: Nonvariational cubic Allen-Cahn equation As in the literature 18 the derivation of Eq. 18 is only sketched, and we find it instructive, here we reproduce it in greater detail.…”
mentioning
confidence: 99%
“…Soon after, it has been considered in a various out of equilibrium systems such as driven liquid crystal [29], coupled oscillators [30], and nonlinear optic cavity [31]. More recently, it has been shown that non-variational terms can induce propagation of fronts in quasi-one-dimensional liquid crystals based devices [32]. Experimental observation of a supercritical transition from stationary to moving localized structures has been realized in two-dimensional planar gas-discharge systems [33].…”
Section: Introductionmentioning
confidence: 99%